Effect of Internal Control System on Financial Performance of Savings and Credit Co-Operatives in Kabale Municipality A Case Study of Lyamujungu SACCO Kabale Branch. - Aheisibwe, Joanita (Kabale University, 2024)
The study investigated the impact of internal control systems on the financial performance of Savings and Credit Cooperatives, focusing on Lyamujungu SACCO in Kabale Municipality. The objectives were to identify the internal control systems employed at Lyamujungu SACCO, to determine the key factors influencing its financial performance, and to examine the relationship between internal controls and financial performance. A descriptive research design was used, with data collected through interviews and questionnaires. The findings on internal control systems in Lyamujungu SACCO highlighted the following components: control environment, risk assessment, information and communication systems, control activities, and monitoring. Key determinants of financial performance identified included loan portfolio quality, capital adequacy, operational efficiency, leadership quality, member satisfaction, and staff productivity. Results showed a strong positive relationship between internal control systems and financial performance at Lyamujungu SACCO. The study recommended that Lyamujungu SACCO’s management establish robust internal control systems, including comprehensive asset listings, approval processes for capital asset purchases, and asset numbering to facilitate location and security. Management should also enforce adequate organizational controls, clarify staff responsibilities, and maintain effective segregation of duties. Additionally, internal controls should be periodically reviewed and enhanced to address any weaknesses, ensuring efficient and effective staff performance.